2014
DOI: 10.2134/jeq2013.11.0452
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Straw or Sawdust to Mitigate Greenhouse Gas Emissions from Slurry Produced by Housed Cattle: A Field Incubation Study

Abstract: The use of housed wintering systems (e.g., barns) associated with dairy cattle farming is increasing in southern New Zealand. Typically, these wintering systems use straw or a woodmix as bedding material. Ammonia (NH) and greenhouse gas (GHG) emissions (nitrous oxide [NO] and methane [CH]) associated with storage of slurry + bedding material from wintering systems is poorly understood. A field incubation study was conducted to determine such emissions from stored slurry where bedding material (straw and sawdus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…The shift in N-based emissions is also consistent with the lower pH with the wood bedding slurry favouring direct N 2 O emissions over indirect NH 3 -N emission (VanderZaag et al 2010). The lower pH may be associated with the acidic nature of wood shavings (van der Weerden et al 2014), although the acidity of the bedding materials alone was not characterized in this study.…”
Section: Nitrous Oxide and Ammonia Emissionssupporting
confidence: 70%
“…The shift in N-based emissions is also consistent with the lower pH with the wood bedding slurry favouring direct N 2 O emissions over indirect NH 3 -N emission (VanderZaag et al 2010). The lower pH may be associated with the acidic nature of wood shavings (van der Weerden et al 2014), although the acidity of the bedding materials alone was not characterized in this study.…”
Section: Nitrous Oxide and Ammonia Emissionssupporting
confidence: 70%
“…Ultimately, greater nutrient concentrations in poultry amendments result in a larger potential for nutrient losses, especially when exposed to rainfall, although this may be affected by differences in animal physiology and feeding regimes, e.g., between chicken and under-studied poultry amendments such as turkey manure (Moreno-Caselles et al 2002;Nicholson, Chambers, and Smith 1996). Finally, the type of bedding found in amendments may affect nutrient cycling and GHG emissions through changes in particle size and oxygen availability (Monteny, Bannink, and Chadwick 2006;Van der Weerden, Luo, and Dexter 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that these influencing factors (i.e., fixed effects) explained about 51% of variance (marginal R 2 ) and 49% of variance was caused by selected publications (i.e., references) and residual error, of which variance of references accounting for 52%. Among references, measurements of NH 3 -N emissions from studies of Dinuccio et al [19] and van der Weerden et al [10] were relatively higher than measurements from studies of Fangueiro et al [18] and Le Riche et al [23] (Supplemental Figure S1).…”
Section: Effects Of Slurry Ph Ts Content Temperature and Storage Duration On Nh 3 -N Emissionsmentioning
confidence: 84%
“…The study of Wood et al [38] reported that NH 3 emissions increased linearly with slurry TS contents varying from 3 to 95 g kg −1 . Van der Weerden et al [10] found the inverse logarithmic relationships between cumulative NH 3 emissions versus the TS contents ranging from 76 to 399 g kg −1 . These results from different studies indicated that the relationship between NH 3 -N emissions and slurry TS contents highly depends on the investigated range of TS contents.…”
Section: Total Solidsmentioning
confidence: 99%
See 1 more Smart Citation